Matching response to need: What makes social networks fit for providing bereavement support? - Aoun, Samar; Breen, Lauren; Rumbold, B.; Christian, K.M.; Same, A.; Abel, J. (PUBLIC LIBRARY SCIENCE, 2019)
© 2019 Aoun et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. The objectives of this study were to explore the goodness of fit between the bereaved peoples’ needs and the support offered by their social networks; to ascertain whether this support was experienced as helpful or unhelpful by bereaved people; and to explore both the types of social networks that offer effective support and the characteristics of the communities that encourage and nurture such networks. This study was based on qualitative interviews from twenty bereaved people, in Western Australia, interviewed in 2013. A framework analysis of these interviews was undertaken using a deductive approach based on the goodness of fit framework. Much of this support is provided informally in community settings by a range of people already involved in the everyday lives of those recently bereaved; and that support can be helpful or unhelpful depending on its amount, timing, function and structure. Improving the fit between the bereaved person’s needs and the support offered may thus involve identifying and enhancing the caring capacity of existing networks. An important strategy for achieving this is to train community members in mapping and developing these naturally occurring networks. Some such networks will include relationships of long standing, others may be circles of care formed during a period of caring. Peer support bereavement networks develop from these existing networks and may also recruit new members who were not part of the caring circle. The findings endorse social models of bereavement care that fit within a public health approach rather than relying solely on professional care. As exemplified by Compassionate Communities policies and practices, establishing collaboration between community networks and professional services is vital for effective and sustainable bereavement care.